Dual band tunable metamaterial absorber based on cuboid ferrite particles. (12th July 2018) - Wang, Wenjie; Wang, Jun; Yan, Mingbao; Wang, Jiafu; Ma, Hua; Feng, Mingde; Qu, Shaobo
Abstract: In this paper, we present the design, fabrication and characterization of a dual band tunable metamaterial absorber (MMA), which can be tuned by the applied magnetic field and modulated by the permittivity of its components. The MMA consists of a periodic array of cuboid ferrites and a metal ground plane. Unlike other MMAs, the proposed MMA avoids utilizing resonant metallic parts, and only employ ferrites as resonators, making fabrication easy and tuning more convenient. When the incident electromagnetic wave and applied magnetic field act on the ferrites simultaneously, cuboid ferrites can produce ferromagnetic resonance. Modulated by its permittivity, the proposed MMA deduces a dual band perfect absorption. The experiment test agrees well with the simulation results and shows two distinct absorption peaks of 99.9% at 9.14 GHz and 97% at 9.48 GHz, respectively. Further investigation shows that the interval of the two distinct absorption peaks can be enlarged by increasing the permittivity of the ferrite, which clearly shows how absorptivity is influenced by its dielectric properties. This work provides an alternative route to realize tunable perfect absorbers with all-ferrite structures. With the artificial design of ferrite materials, the tunable perfect absorbers can be designed freely and are well served in a high power environment.